Capecitabine and lapatinib for the first‐line treatment of metastatic/recurrent head and neck squamous cell carcinoma - Weiss, Jared M.; Bagley, Stephen; Hwang, Wei‐Ting; Bauml, Joshua; Olson, Juneko Grilley; Cohen, Roger B.; Hayes, David Neil; Langer, Corey (Cancer, 2016)
BACKGROUND The combination of cisplatin, 5‐fluorouracil, and cetuximab is a standard treatment for patients with recurrent/metastatic head and neck cancer, with a high rate of toxicity. Identifying less toxic, equally effective regimens is imperative. Therefore, in the current study, the authors investigated first‐line treatment with an all‐oral regimen of capecitabine and lapatinib. METHODS Patients were required to have incurable head and neck cancer of any primary site other than the nasopharynx, an Eastern Cooperative Oncology Group performance status (ECOG PS) of 0 to 2, and no prior exposure to capecitabine or lapatinib. Subjects were treated with capecitabine at a dose of 1000 mg/m2 twice daily and lapatinib at a dose of 1250 mg daily. Capecitabine was administered for 14 days of each 21‐day cycle for 4 cycles. Lapatinib was administered daily until disease progression. The primary outcome was overall survival. RESULTS A total of 44 subjects were accrued between November 13, 2009 and April 29, 2014. Approximately 38.6% of the sample had an ECOG PS of 0, 52.3% had an ECOG PS of 1, and 9.1% had an ECOG PS of 2. Approximately 81.8% were male and the median age of the patients was 62 years. Prior attempts at curative treatment with chemotherapy had been used in 68.2% of patients (platinum was used in 55.8%). There was no grade 5 toxicity noted (toxicity was graded according to National Cancer Institute Common Terminology Criteria for Adverse Events [version 3.0]). The most common adverse events were diarrhea (18.2% of patients with grade 3) and rash (13.6% of patients with grade 3). The primary objective was met; the median overall survival was 10.7 months (90% confidence interval [90% CI], 8.7‐12.9 months). The overall response rate was 25% (90% CI, 15%‐38%). The median progression‐free survival was 4.2 months (90% CI, 3.6‐5.1 months). The results were not substantially different when subdivided by p16 status. Only 2 patients were positive for human epidermal growth factor receptor 2 by immunohistochemistry. CONCLUSIONS The current study met its primary objective of survival comparable to the combination of cisplatin, 5‐FU and cetuximab regimen, and the toxicity of this all‐oral regimen was tolerable. Cancer 2016;122:2350–2355. © 2016 American Cancer Society. In the current study, patients receiving first‐line treatment of metastatic/recurrent head and neck squamous cell cancer were treated with the all‐oral regimen of capecitabine and lapatinib. The median progression‐free survival was 4.2 months and the median overall survival was 10.7 months.